Therapeutic Perspectives in Otosclerosis: Surgical Treatment versus Hearing Aids - a Retrospective Observational Study - Amorim, Miguel Ângelo (2025)
Introduction: Otosclerosis is one of the causes of transmission hearing loss in adults, there are two types of rehabilitation, surgery or hearing aids use. Objective: Evaluate the results of rehabilitation with surgery and hearing aids use in otosclerosis treatment, comparing it with the reduction of air-bone gap. Method: For this study were selected 64 patients, 46 of them in the list of surgical treatment in ENT department of Hospital S. João de Deus, 18 patients were rehabilitated with hearing aids. Results: Surgery was performed in 71,9% of the cases and hearing aids use in 28,1%, shown medium results in reduction of air-bone gap better in patients with surgical treatment. Conclusion: Surgery was the rehabilitation technic more efficient reducing air-bone gap.